Evaluation of possible failure of the mononuclear phagocyte system after total splenectomy in rats - Marques,Ruy Garcia (2004)
Young and adult Wistar rats were submitted to total splenectomy and compared to animals not submitted to any surgical manipulation in order to evaluate the phagocytic function of spleen. The animals were infected with Escherichia coli labeled with technetium-99m and killed 20 minutes later. Liver, lung, spleen and a blood clot sample were taken. No significant differences were found in the percentage of bacterial radioactivity uptake in mononuclear phagocyte system (MPS) organs in young and adult splenectomized rats. However, phagocytosis index by macrophages of MPS organs was smaller in splenectomized animals than in control group. Splenectomized rats were associated with a higher blood bacterial radioactivity uptake than animals of the control group (p<0.0001) due to a larger bacterial remnant in the bloodstream. This finding suggested that some failure in the MPS occurred in the absence of the spleen, demonstrating the need to develop alternative surgical techniques for total splenectomy.